2016
DOI: 10.1002/slct.201601140
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Transfer Catalysis with Ionene Polymers

Abstract: Ionene polymers were found to be versatile phase-transfer catalysts for a variety of different reactions like a-alkylation reactions or Michael addition reactions. Reasonably low catalyst loadings allowed us to obtain the target products under operationally simple biphasic conditions at ambient temperature and the ionenes can be recovered and reused by simple filtration.Ionene polymers constitute an important class of polyelectrolytes [1] in which quaternary ammonium groups form part of the polymer backbone. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…Cationic polyelectrolytes bearing quaternary ammonium in the backbone constitute an important group of highly charged polymers, named ionenes, with potential uses in the biomedical [1][2][3] and catalytic applications. [4][5][6][7] The synthesis of new ionene polymers (Scheme 1) containing 1,4-diazabicyclo[2.2.2]octane (DABCO) and N,N'-(xphenylene)dibenzamide (x= ortho-/ meta-/ para-) was described and their gelation capacity in aqueous media was reported by some of us. 8,9 It was found that the topology of this polymers plays a fundamental role in their self-assembly properties in pure water 8 and in aqueous solutions with different acidic pH and ionic strength.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic polyelectrolytes bearing quaternary ammonium in the backbone constitute an important group of highly charged polymers, named ionenes, with potential uses in the biomedical [1][2][3] and catalytic applications. [4][5][6][7] The synthesis of new ionene polymers (Scheme 1) containing 1,4-diazabicyclo[2.2.2]octane (DABCO) and N,N'-(xphenylene)dibenzamide (x= ortho-/ meta-/ para-) was described and their gelation capacity in aqueous media was reported by some of us. 8,9 It was found that the topology of this polymers plays a fundamental role in their self-assembly properties in pure water 8 and in aqueous solutions with different acidic pH and ionic strength.…”
Section: Introductionmentioning
confidence: 99%
“…These salts were prepared by carrying out a chloride to iodide exchange of the initially used salts (see the supporting information for details). Very interestingly, this lead to a significant improvement in case of the A and B series (entries [17][18][19][20], which performed rather slow with chlorides only. On the other hand, those polymers that performed well for the chloride salts already (i.e.…”
Section: Resultsmentioning
confidence: 94%
“…To investigate the influence of the counter anion we next tested the corresponding iodide-based polymers (entries [17][18][19][20][21][22][23][24]. These salts were prepared by carrying out a chloride to iodide exchange of the initially used salts (see the supporting information for details).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations